“Estimación de mérito genético total del programa de mejoramiento genético sostenible de bovinos de leche en la parroquia Belisario Quevedo” - Gálvez Cisneros, Yadira Fernanda (2023)
Belisario Quevedo Parish is considered an agricultural territory where there is high-yield dairy production. However, farm owners do not receive a fair amount of money to achieve adequate sustainability, even though there has been an increase in the milk price. This means that the inversion that goes towards animals is unsustainable to achieve proper care and maintenance. Despite this, some of the innate sustainable characteristics that bovines have are crucial for each property’s care and maintenance. Therefore, the parish milking herd's total genetic merit rate was estimated through productive economic parameters, genetic value, and selection response with the purpose of selecting sustainable bovine herds in order to spread their genetic characteristics and enhance their offspring. Fifteen farms participating in the project were assessed through productive parameters of the milking herd, such as density, weight gain, milk production, quality, and economic investment by the owners, keeping in mind that the average raw price of raw milk is 0.41 cents per liter, the production cost of milk is 0.26 cents per liter, and the benefit is 0.15 cents. The objective was established through the data obtained regarding weight gain, production, and milk density with respect to the feeding cost for the purpose of selecting a sustainable bovine herd. According to the data analysis, the feeding cost had a greater economic weight with a 73,90% share of the average total spend of the parish, as an examination of the selected parameters demonstrated no correlation during the 3-month data collection from different farms. At the same time, the breeding value with respect to the density was estimated with an average of -0.066g/L and an average confidence index of 54%. When it comes to milk production, the average is -163.50 L/lactation with an average confidence index of 62%, and the weight gain is an average of 25.64 grams with a 54% confidence index. Finally, the selection response allowed us to select one animal that met the goal of decreasing the feeding costs in the parish. The same animal had an ADG (average daily gain) of 535.27 gr, a milk production per lactation of 3833.53 L, and a density of 1.024g/mL.